The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.12659/msm.920255
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nomogram for Predicting Blood Transfusion Risk After Hemiarthroplasty for Femoral Neck Fractures in Elderly Patients

Abstract: The aim of this study was to determine the risk factors and develop a nomogram for blood transfusions after hemiarthroplasty (HA) in patients with femoral neck fractures (FNFs). Material/Methods:We performed a retrospective study including consecutive elderly FNF patients treated by HA between January 2015 and December 2017. Perioperative information was obtained retrospectively, uni-and multivariate regression analyses were conducted to determine risk factors for blood transfusion, and a nomogram model was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
10
10
2
Order By: Relevance
“…In this study, the preoperative Hb of the blood transfusion group was (113.9 ± 14.0) g/L, which was signi cantly lower than the preoperative Hb (128.2 ± 12.8) g/L of the non-transfusion group (p < 0.05). This result is consistent with many previous studies [7,9,13] . Adunsky A et al [14] found that patients with preoperative Hb lower than 120 g/L have a 5-fold increase in the risk of postoperative blood transfusion.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In this study, the preoperative Hb of the blood transfusion group was (113.9 ± 14.0) g/L, which was signi cantly lower than the preoperative Hb (128.2 ± 12.8) g/L of the non-transfusion group (p < 0.05). This result is consistent with many previous studies [7,9,13] . Adunsky A et al [14] found that patients with preoperative Hb lower than 120 g/L have a 5-fold increase in the risk of postoperative blood transfusion.…”
Section: Discussionsupporting
confidence: 94%
“…The IBL of the transfusion group was (231.8 ± 97.0) ml, which was signi cantly higher than that of the non-transfusion group (190.5 ± 89.9) ml (p < 0.05). It is consistent with the results of Wang JQ et al [9] . Under normal circumstances, the amount of intraoperative blood loss increases the risk of blood transfusion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the preoperative Hb of the blood transfusion group was (113.18 ± 14.69) g/L, which was signi cantly lower than the preoperative Hb (128.80 ± 12.41) g/L of the nontransfusion group (p < 0.05). This result is consistent with many previous studies [7,9,13] . Adunsky A et al [14] found that patients with preoperative Hb lower than 120 g/L have a 5-fold increase in the risk of postoperative blood transfusion.…”
Section: Discussionsupporting
confidence: 94%
“…Meanwhile, data on the transfusion of RBCs before surgery and the clinical significance of intraoperative and postoperative risk factors such as operation time, intraoperative blood loss, and postoperative laboratory indicators are limited. Studies have been conducted to predict blood transfusion in joint surgery, craniofacial surgery, and obstetric surgery by developing clinical prediction models combined with patients' preoperative risk factors ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%